Effect of Brand Digitalization of E-Mas Transactions: E-Mas Features On The Mobile BSI Maqashid Syariah Framework - Arfarizan, Arfarizan; Hasan, Asyari (Devotion : Journal of Research and Community Service, 2023)
This study aims to examine how gold transactions implementation through the e-mas feature on BSI mobile at Bank Syariah Indonesia and find out whether gold transactions through the e-mas feature are in accordance with the concept of sharia maqashid. This research uses qualitative analysis methods that explain gold transactions implementation through the e-mas feature on BSI mobile at Bank Syariah Indonesia and the suitability of gold transactions contained in the e-Mas feature with the concept of sharia maqashid (Dharuriyyah, Hajiyat and Tahsiniyat). The division of dharuriyyah is categorized into 5 basics, such as 1) Protecting religion, 2) Protecting souls, 3) Protecting offspring, 4) Protecting reason and 5) Protecting property. Data collection techniques are literature studies, documentation studies, discussions and intuitive subjective. The results show digital innovation "e-mas BSI Mobile" is in under the concept of sharia maqashid and can help the public to conduct gold transactions at Bank Syariah Indonesia (BSI) and support halal needs based on sharia maqashid.